A monitoring system of sand mining in large rivers and its application to the Ayeyarwady (Irrawaddy) River, Myanmar - Gruel, Charles R. (2021)
Sand mining is one of the major sustainability challenges of the 21st century. Rates of extraction are surpassing sand supply, and ensuing sand starvation is adversely impacting channel-floodplains and deltas. Therefore, quantifying sand mining’s location and extent, through global monitoring and detection, particularly in fluvial systems, is becoming a priority. Sand mining by dredges and barges (extraction of sand and secondarily gravel) in South East Asian rivers, including illegal sand mining, has become rampant, and a monitoring system is not yet in place. Here, we present a high-resolution remote sensing-based mining monitoring system for sand mining in fluvial systems. We used Sentinel-1 mission, a radar component of the Copernicus joint initiative of the European Commission (EC) and the European Space Agency (ESA). The system, tested in the Ayeyarwady, the second largest river in SE Asia, detects sand mining by barges almost in real-time with a satisfactory accuracy level. An additional advantage of the monitoring system is that it does not incur any costs, making it accessible to multiple users, decision-makers, and stakeholders.